Assessment of Natural Radionuclide Ingestion Through Foodstuffs Cultivated Around the Sokoto Cement Production Facility, Northwestern Nigeria. - Abba, Lawal; Dahuwa, Dahiru (FUDMA Journal of Sciences, 2026)
Exposure to radiation is a natural phenomenon unavoidable to  human environment. Ionizing radiation is received from naturally occurring radionuclides in water, air, soil and food. Ingestion is one of the major pathways through which these radionuclides enter the human body. Assessment of natural radionuclide on twelve (12) samples, four (4) each of leafy vegetables, cereals and tuber crops cultivated and consumed around the cement production facility of Sokoto has been carried out using a 76mm by 76mm lead-shielded Sodium Iodide detector (NaI(Tl)) located at the Centre for Energy, Research and Training (CERT), Ahmadu Bello University Zaria, Nigeria. The overall mean activity concentration of the radionuclides in the  samples of leafy vegetables, cereals and tuber crops  were 39.8904±6.1347 Bqkg-1 for 226Ra, 57.6631±5.5907 Bqkg-1 for 232Th and  Bqkg-1 for 168.6004±8.4195 40K. All values of consequential effective dose for both adults and children due to consumption of radionuclides in food stuffs were higher than recommended value of 1 mSvyr-1, except for leafy vegetable in children. Hence, intermittent monitoring of radioactivity level in food stuffs grown in the study area is recommended.
Keywords: Natural Radioactivity; Effective Dose; Food Stuffs; Gamma Spectrometry; Sokoto Cement Company